Dissociation of leukocyte alkaline phosphatase from the bactericidal activity of neutrophils. - DeChatelet, L R (1979)
We have identified an apparently healthy individual with no history of repeated infections whose neutrophils were virtually devoid of alkaline phosphatase activity by either spectrophotometric or histochemical assay. His cells showed normal bactericidal activity toward both Staphylococcus aureus and Escherichia coli when tested in vitro. We have also demonstrated that L-p-bromolevamisole, a potent inhibitor of alkaline phosphatase in many tissues, is likewise an effective inhibitor of the neutrophilic enzyme. Concentrations of this compound which caused nearly complete inhibition of the neutrophilic enzyme did not impair the ability of intact cells to kill bacteria. These results suggest that leukocyte alkaline phosphatase is not required for the normal bactericidal activity of neutrophils.